The Design of Automatic Soil pH Control System on Aloe vera Cultivation with an Integration of Internet of Things (IoT) - Renny Eka Putri; Widi Darmadi; Dinah Cherie; Aninda Tifani Puari (The University of Lampung, 2023)
Machine learning and internet of thing (IoT) would be the best option for monitoring the appropriate soil pH condition. This research aimed on the design an automatic soil pH control system based on IoT for monitoring the cultivation of Aloe vera plants. The Telegram application was occupied as an IoT platform and was connected to a free and easy access application, Node MCU 8266. Furthermore, relay, Arduino Uno and smartphone were occupied in the system. According to the system testing, soil pH sensor readings are close to the actual value as evidenced by the linear regression value or R2 on sensors 1 and 2 which are close to 1. Meanwhile, the total percentage of system performance testing was 93% while the error value for the pH sensors were 0.96 and 1.6% for sensor 1 and sensor 2, respectively. Furthermore, the plant observations showed that the average leaf length of plants with a control system was 24.78 cm while with the manual system was 23.11 cm. From the results of the T test obtained, it was found that the control system applied to Aloe vera cultivation had a significant effect on the growth and development of Aloe vera compared to Aloe vera plants with a manual system. Keywords: Aloe vera, Control system, Internet of things (IoT), Soil pH sensor